Can you resubmit your question so that I can give you a reasonable answer
Answer:
Step-by-step explanation:
You need to be specific. Did the weight decrease by 60 tons or 60 pounds? I assume tons, but in math, you can't assume.
This problem seems overly simple, so I am wondering if some information is missing. With the given information and assuming the decrease was in fact 60 tons, you would have:
125,890 - 60 = 125,830 tons
Answer:
a:36 b:30
Step-by-step explanation:
A:180-56, since it is a straight line.
180-124-20= 36
B:180-120=60
60+3x+1x=180
60+4x=180
4x=120
x=30
Answer:(-2,0) and (3,0)
Step-by-step explanation:im not sure if its correct but it should be
Answer:
(a) ¬(p→¬q)
(b) ¬p→q
(c) ¬((p→q)→¬(q→p))
Step-by-step explanation
taking into account the truth table for the conditional connective:
<u>p | q | p→q </u>
T | T | T
T | F | F
F | T | T
F | F | T
(a) and (b) can be seen from truth tables:
for (a) <u>p∧q</u>:
<u>p | q | ¬q | p→¬q | ¬(p→¬q) | p∧q</u>
T | T | F | F | T | T
T | F | T | T | F | F
F | T | F | T | F | F
F | F | T | T | F | F
As they have the same truth table, they are equivalent.
In a similar manner, for (b) p∨q:
<u>p | q | ¬p | ¬p→q | p∨q</u>
T | T | F | T | T
T | F | F | T | T
F | T | T | T | T
F | F | T | F | F
again, the truth tables are the same.
For (c)p↔q, we have to remember that p ↔ q can be written as (p→q)∧(q→p). By replacing p with (p→q) and q with (q→p) in the answer for part (a) we can change the ∧ connector to an equivalent using ¬ and →. Doing this we get ¬((p→q)→¬(q→p))